Speciation analysis of organolead compounds in greenland snow at the femtogram-per-gram level by capillary gas chromatography/atomic emission spectrometry - Lobinski, Ryszard; Boutron, C.F.; Candelone, J.-P.; Hong, S.; Szpunar-Lobinska, J.; Adams, F.C. (HAL CCSD, 1993)
International audience A method for comprehensive speciation analysis of organolead compounds in polar snow at levels down to femtograms per gram is developed. The analytes are preconcentrated (250:1) in a single-step extraction, derivatized by propylation using a Grignard reagent, and analyzed by capillary gas chromatography with microwave-induced plasma atomic emission detection (GC-MIP AED) after further on-line preconcentration (50:1). Extraction and derivatization efficiencies of organolead species at subpicogram per gram levels and sources of the blank are extensively discussed. A number of snow samples collected at different locations in Greenland are analyzed, providing the first data on organolead levels in polar snow. Tri- and diethyllead species are the only compounds found in the majority of the samples.